What are the mechanisms of effect of group antenatal care? A systematic realist review and synthesis of the literature - Anita Mehay; Giordana Da Motta; Louise Hunter; Juliet Rayment; Meg Wiggins; Penny Haora; Christine McCourt; Angela Harden (BMC, 2024)
Abstract Background There is growing interest in the benefits of group models of antenatal care. Although clinical reviews exist, there have been few reviews that focus on the mechanisms of effect of this model. Methods We conducted a realist review using a systematic approach incorporating all data types (including non-research and audiovisual media), with synthesis along Context-Intervention-Mechanism-Outcome (CIMO) configurations. Results A wide range of sources were identified, yielding 100 relevant sources in total (89 written and 11 audiovisual). Overall, there was no clear pattern of 'what works for whom, in what circumstances' although some studies have identified clinical benefits for those with more vulnerability or who are typically underserved by standard care. Findings revealed six interlinking mechanisms, including: social support, peer learning, active participation in health, health education and satisfaction or engagement with care. A further, relatively under-developed theory related to impact on professional practice. An overarching mechanism of empowerment featured across most studies but there was variation in how this was collectively or individually conceptualised and applied. Conclusions Mechanisms of effect are amplified in contexts where inequalities in access and delivery of care exist, but poor reporting of populations and contexts limited fuller exploration. We recommend future studies provide detailed descriptions of the population groups involved and that they give full consideration to theoretical underpinnings and contextual factors. Registration The protocol for this realist review was registered in the International Prospective Register of Systematic Reviews (PROSPERO CRD42016036768).